Associations of night-time road traffic noise with carotid intima-media thickness and blood pressure: The Whitehall II and SABRE study cohorts. (January 2017) - Halonen, Jaana I.; Dehbi, Hakim-Moulay; Hansell, Anna L.; Gulliver, John; Fecht, Daniela; Blangiardo, Marta; Kelly, Frank J.; Chaturvedi, Nish; Kivimäki, Mika; Tonne, Cathryn
Abstract: Background: Road traffic noise has been linked to increased risk of stroke, for which hypertension and carotid intima-media thickness (cIMT) are risk factors. A link between traffic noise and hypertension has been established, but there are few studies on blood pressure and no studies on cIMT. Objectives: To examine cross-sectional associations for long-term exposure to night-time noise with cIMT, systolic blood pressure (SBP), diastolic blood pressure (DBP) and hypertension. Methods: The study population consisted of 2592 adults from the Whitehall II and SABRE cohort studies living within Greater London who had cIMT, SBP and DBP measured. Exposure to night-time road traffic noise (A-weighted dB, referred to as dBA) was estimated at each participant's residential postcode centroid. Results: Mean night-time road noise levels were 52 dBA (SD = 4). In the pooled analysis adjusted for cohort, sex, age, ethnicity, marital status, smoking, area-level deprivation and NOx there was a 9.1 μm (95% CI: − 7.1, 25.2) increase in cIMT in association with 10 dBA increase in night-time noise. Analyses by noise categories of 55–60 dBA (16.2 μm, 95% CI: − 8.7, 41.2), and > 60 dBA (21.2 μm, 95% CI: − 2.5, 44.9) vs. < 55 dBA were also positive but non-significant, expect among those not using antihypertensive medication and exposed to > 60 dBA vs. < 55 dBA (32.6 μm, 95% CI: 6.2, 59.0). Associations for SBP, DPB and hypertension were close to null. Conclusions: After adjustments, including for air pollution, the association between night-time road traffic noise and cIMT was only observed among non-medication users but associations with blood pressure and hypertension were largely null. Highlights: This is the first study on associations between road traffic noise and cIMT. Night-time road traffic noise was associated with higher cIMT in non-medication users. Association between road traffic noise and blood pressure was close to null. Association between road traffic noise and hypertension was close to null.